METHODS TO INCREASE INTAKE OF GLIRICIDIA LEAVES (GLIRICIDIA SEPIUM) BY SHEEP - KARDA, I W.; SPUDIATI, SPUDIATI (Majalah Ilmiah Peternakan; Vol 9 No 3 (2006), 2012)
SUMMARY Three trials were conducted to investigate the intake of oven-dried gliricidia by sheep, namely trial 1, addition of polyethylene glycol (PEG), trial 2, pretreatments, and trial 3 addition of additives. In the first trial, six rumen fistulated sheep were used to compare two dietary treatments in a change over design to study whether infusion of polyethelene glycol (PEG) into the rumen might increase intakes of gliricidia leaf as tannin in the leaf was believed to limit its intake. In the second trial, four sheep were used to compare four dietary treatments in a latin square design to study whether reheating or freezing the already oven-dried gliricidia leaf might increase its intake by the animals. On the other hand, the third trial was aimed to supplement the sheep with various supplements which are believed to be able to increase the taste of the leaf by the animals. These supplements were wheat millrun, molases, grass hay, cottonseed meal, palm kernel meal, or barley grain. For this reason, ten sheep were used to compare seven dietary treatments in a randomised complete block design. Differences between means were examined by analysis of variance using the General Linear Model procedure of the Statistical Analysis System. The results showed that neither administration of PEG into the rumen nor pretreatments (reheating or freezing) increased intake of gliricidia leaf by sheep. However, only mixing gliricidia with molasses increased the intake of the leaf by sheep over the control diet (gliricidia alone) over the six hours feeding period (43 vs 74 g DM).